Effects of tibolone and its metabolites on prolactin and insulin-like growth factor binding protein-1 expression in human endometrial stromal cells. (May 2015) - Guzel, Elif; Buchwalder, Lynn; Basar, Murat; Kayisli, Umit; Ocak, Nehir; Bozkurt, Idil; Lockwood, Charles J.; Schatz, Frederick
Abstract The effects of the postmenopausal replacement steroid tibolone and its 3α-, 3β-OH and Δ-4 tibolone metabolites were evaluated on progesterone receptor-mediated classic decidualization markers insulin-like growth factor binding protein-1 (IGFBP-1) and prolactin expression in human endometrial stromal cells (HESCs). Supernatants of conditioned medium or erxtracted RNA from experimental cell incubations of confluent HESCs were subjected to ELISAs, Western blot analysis and RT/PCR, and results were statisically assesed. Over 21 days, specific ELISAs observed linear increases in secreted IGFBP-1 and prolactin levels elicited by tibolone and its metabolites. Cultured HESCs were refractory to E2 and dexamethasone, whereas tibolone and each metabolite exceeded medroxyprogesterone acetate in significantly elevating IGFBP-1 and prolactin output. Anti-progestins eliminated IGFBP-1 and prolactin induction by tibolone and its metabolites. Immunoblotting and RT/PCR confirmed ELISA results. These observations of IGFBP-1 and prolactin expression: (a) indicate the relevance of cultured HESCs in evaluating the chronic effects of tibolone administration to women; (b) are consistent with PR-mediated endometrial atrophy and protection against endometrial bleeding despite the persistence of circulating ER-binding, but not PR-binding metabolites following tibolone administration to women.